The Impact of Plato’s and Aristotle’s Mimesis Concept on the Cinema - Hayati, Vahid (International Journal of Psychosocial Rehabilitation, 2021)
Among the important theories in the philosophy of art, Mimesis and imitation can be considered as one of the most important approaches along with theories such as expressionism, institutional theory and other theories, whose description and explanation are the basis of many philosophical discussions of art. Plato and Aristotle have a special place among the philosophers who have dealt with Mimesis. Although the term has evolved over the centuries, the concept of mimesis has sometimes been marginalized by the importance of the creative imagination in the Romanticism approach, but it has always maintained its place among the art theories. This study examines the concept of mimesis in Plato’s and Aristotle’s speech and, while explaining this concept in the field of art from the perspective of these two philosophers, and analyzes the impact and placement of this concept on cinema through Realism using descriptive and analytical method. As a result, Mimesis’s semantic in the history of art evolution and the traces of this concept in cinema are outlined in this research under the theory of realism and formalism in cinema